New Oral Anticoagulants for Acute and Long-Term Treatment of Haemodynamically Stable Pulmonary Embolism - Masotti, Luca; Lorenzini, Gianni; Landini, Giancarlo; Bettoni, Niccolò; Panigada, Grazia; Cappelli, Roberto (Global Journal of Respiratory Care, 2014)
Historically, standard treatment of haemodynamically stable pulmonary embolism (PE) in the acute phase consists in parenteral anticoagulants overlapped with oral anticoagulants vitamin K antagonists (VKAs) for at least 5-7 days followed by VKAs alone when their therapeutic range is reached and prolonged for at least three-six months (long term phase). However standard treatment has many pharmacological and practical limitations. For overcoming these limitations, new anticoagulant drugs with better pharmacological profile and easier to use, have been manufactured and tested in pre-clinical and clinical trials with the aim to reach at least non inferiority compared to standard treatment. In the setting of PE, new oral anticoagulants (NOACs), direct inhibitors of thrombin (dabigatran) or activated factor X (apixaban, edoxaban, rivaroxaban) have been tested in the acute and long-term phases of treatment in phase III randomized clinical trials (RCTs). Rivaroxaban (EINSTEIN-PE study) and apixaban (AMPLIFY study) have been tested directly from diagnosis, dabigatran (RE-COVER I and II studies) and edoxaban (HOKUSAI study) starting after 7-10 days of standard treatment. Overall, these trials have demonstrated that NOACs are effective and safe at least as standard treatment, promising a revolutionary approach to PE treatment in acute/sub-acute PE based on single drug approach or rapid switch from parenteral to oral anticoagulation. In this paper the Authors focus on phase III RCTs on NOACs in the acute and long-term phases of PE treatment, highlighting the first two weeks of treatment.